Hubungan Dukungan Keluarga Dengan Kualitas Hidup Pada Lansia Di Panti Lansia May Sam Fureru Home Nursing Kanagawa Jepang Tahun 2023 - Deni Candra; Sancka Stella G. Shihura; Weslei Darli (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2024)
Elderly becomes an aging process that as it ages causes various deterioration of body functions and a decrease in the level of independence, if this condition lasts long it will have an impact on the quality of life of the elderly. Quality of life in the elderly is important because it is an indicator of successful aging. This quality of life is influenced by various factors, one of which is family support. Family support is included in the supporting factors that can influence a person's behavior and lifestyle so that it has an impact on their health status and quality of life. The purpose of this study was to determine the relationship between family support and quality of life in the elderly at May Sam Fureru Home Nursing Kanagawa, Japan. Type of correlational research with a cross sectional approach. The population and sample were all elderly people in the elderly home of May Sam Fureru Home Nursing Kanagawa Japan as many as 60 respondents using the sampling technique is total sampling. The family support questionnaire uses the standardized Family Support Scale (FSS) instrument, on quality of life using the WHO Quality of life-BREEF. Data analysis using Yates correction test. Univariate analysis showed that most respondents did not get family support by 55.0%, and in quality of life it was found that most respondents had a quality of life that was sufficient at 46.7%. There is a relationship between family support and quality of life in the elderly at May Sam Fureru Home Nursing Kanagawa Japan in 2023. It is hoped that it can be used as a reference material for nurses to carry out nursing care by involving families to help care, and serve as evidence-based practice for future researchers to develop further research.